Efficient In Vitro Generation of IL-22-Secreting ILC3 From CD34+ Hematopoietic Progenitors in a Human Mesenchymal Stem Cell Niche - Bennstein, Sabrina B.; Weinhold, Sandra; Degistirici, Özer; Oostendorp, Robert A. J.; Raba, Katharina; Kögler, Gesine; Meisel, Roland; Walter, Lutz; Uhrberg, Markus (Frontiers in Immunology, 2021)
Innate lymphoid cells (ILCs) and in particular ILC3 have been described to be vital for mucosal barrier functions and homeostasis within the gastrointestinal (GI) tract. Importantly, IL-22-secreting ILC3 have been implicated in the control of inflammatory bowel disease (IBD) and were shown to reduce the incidence of graft-versus-host disease (GvHD) as well as the risk of transplant rejection. Unfortunately, IL-22-secreting ILC3 are primarily located in mucosal tissues and are not found within the circulation, making access to them in humans challenging. On this account, there is a growing desire for clinically applicable protocols for in vitro generation of effector ILC3. Here, we present an approach for faithful generation of functionally competent human ILC3s from cord blood-derived CD34+ hematopoietic progenitors on layers of human mesenchymal stem cells (MSCs) generated in good manufacturing process (GMP) quality. The in vitro-generated ILC3s phenotypically, functionally, and transcriptionally resemble bona fide tissue ILC3 with high expression of the transcription factors (TF) Ror𝛾T, AHR, and ID2, as well as the surface receptors CD117, CD56, and NKp44. Importantly, the majority of ILC3 belonged to the desired effector subtype with high IL-22 and low IL-17 production. The protocol thus combines the advantages of avoiding xenogeneic components, which were necessary in previous protocols, with a high propensity for generation of IL-22-producing ILC3. The present approach is suitable for the generation of large amounts of ILC3 in an all-human system which could facilitate development of clinical strategies for ILC3-based therapy in inflammatory diseases and cancer.